Beliefs about Maternal Labor Supply - Teodora Boneva; Marta Golin; Katja Kaufmann; Christopher Rauh (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper provides representative evidence on the perceived returns to maternal labor supply. We design a novel survey to elicit subjective expectations, and show that a mother's decision to work is perceived to have sizable impacts on child skills, family outcomes, and the future labor market outcomes of the mother. Examining the channels through which the impacts are perceived to operate, we document that beliefs about the impact of additional household income can account for some, but not all, of the perceived positive effects. Beliefs about returns substantially vary across the population and are predictive of labor supply intentions under different policy scenarios related to childcare availability and quality, two factors that are also perceived as important. Consistent with socialization playing a role in the formation of beliefs, we show that respondents whose own mother worked perceive the returns to maternal labor supply as higher.
Keywords: J22; J13; I26; 330; subjective expectations; maternal labor supply; childcare; child penalties